2023
DOI: 10.1002/jmv.28997
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of SARS‐CoV‐2 reinfection, a multicenter cohort study in Shanghai, China

Abstract: During March 2022 to January 2023, two Omicron waves hit Shanghai and caused a massive number of reinfections. To better understand the incidence and clinical characteristics of SARS‐CoV‐2 reinfection in Shanghai, China, we conducted a multicenter cohort study. COVID‐19 patients first infected with BA.2 (March 1, 2022–May 23, 2022) who were quarantined in Huashan Hospital, Renji Hospital, and Shanghai Jing'an Central Hospital were followed up for reinfection from June 1, 2022 to January 31, 2023. Of 897 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In this study, the reinfection rate among HCWs was 11.5%. This is similar to previous studies [ 22 , 23 ]. The reasons for COVID-19 reinfection are multifaceted, primarily including low antibody levels, the shortened duration of immune protection provided by antibodies, the mutation of viral strains, non-adherence to epidemic prevention measures by the population, hesitancy towards vaccination, and public fatigue due to the prolonged pandemic.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the reinfection rate among HCWs was 11.5%. This is similar to previous studies [ 22 , 23 ]. The reasons for COVID-19 reinfection are multifaceted, primarily including low antibody levels, the shortened duration of immune protection provided by antibodies, the mutation of viral strains, non-adherence to epidemic prevention measures by the population, hesitancy towards vaccination, and public fatigue due to the prolonged pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…It is also relevant to note that the younger HCWs are more susceptible to infection and reinfection compared to relatively older ones in Omicron wave [ 37 ]. Previous studies have reported that females are more susceptible to COVID-19 [ 12 , 38 ] and have a higher risk of reinfection [ 23 ]. In the results of a previous study, most of cases are nurses (48%), followed by physicians (25%) and other HCWs (23%) [ 39 ], which are similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both types of study have shown that natural and artificial immunity both wane over time and have led to the adaptation of recommendations regarding vaccination schedules [ 8 , 17 , 19 , 27 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Common epidemiological indicators of frequency in other studies showed increases in the number of reinfections and primo-infections in the Omicron era, similar to our study [ 25 , 26 , 43 , 44 ]. The previously published study on the first SARS-CoV-2 infection, on the same population of HCWs, showed a higher severity of the cases registered in HCWs from the high-risk departments [ 18 ].…”
Section: Discussionsupporting
confidence: 91%